Beyond Curriculum: How Teacher Personalities Shape Student Learning Experiences - Abou Assali, Mouna (Research Journal in Advanced Humanities, 2025)
Within educational psychology, the influence of instructor’s character traits on student learning outcomes has become more widely acknowledged, posing a challenge to the conventional emphasis on curriculum design and pedagogical strategies alone. The present research integrates extant literature and empirical data to investigate the complex correlation between educator’s character traits and student learning, concentrating on the consequences for instructional design and policy development. Educator’s character traits have a weighty consequence on student education and the classroom environment. The results highlight how crucial it is to consider teacher personality when hiring, selecting, and developing new teachers. They also guide development and encourage classroom environments that help students achieve their goals. In addition, incorporating teacher personality traits into the theoretical framework of educational psychology enhances our comprehension of the reciprocal nature of teacher-student interaction and effective teaching practices.